ANALYSIS OF METAPHOR AND METANYMY IN ENGLISH AND UZBEK (Uzbek Scholar Journal, 2024)
This article delves into the intricate realms of metaphor and metonymy, two fundamental aspects of language and cognition, in both English and Uzbek languages. Through a comprehensive comparative analysis, it explores how these figurative devices are utilized, conceptualized, and expressed in the linguistic structures and cultural contexts of both languages. Drawing on linguistic theories, cognitive linguistics, and corpus-based studies, this article aims to shed light on the similarities, differences, and cultural nuances inherent in the use of metaphor and metonymy in English and Uzbek.